2015
DOI: 10.1158/1940-6207.capr-15-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin on Breast Ductal Carcinoma In Situ Proliferation in a Randomized Presurgical Trial

Abstract: Metformin is associated with lower breast cancer risk in epidemiologic studies and showed decreased proliferation in HER2-positive breast cancer in a presurgical trial. To provide insight into its preventive potential, we measured proliferation by Ki-67 labeling index (LI) of intraepithelial lesions surrounding breast cancer. We randomly assigned 200 nondiabetic patients diagnosed with invasive breast cancer in core biopsies to metformin, 1,700 mg or placebo once daily for 28 days before surgery. Upon surgery,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The authors concluded that a lower Ki-67 LI in ductal hyperplasia under metformin in women with abdominal obesity, the hallmark of insulin resistance, in line with cancer tissue. Thus, metformin selectively decreased Ki-67 in Human Epidermal Growth factor Receptor 2 (HER2)-positive cancers and in women with extra markers of insulin resistance [11]. Interestingly, recent study confirmed that patients with low Ki-67 expressions, negative epidermal growth factor receptor staining and preoperative positive urine cytology appear to be more sensitive to intravesical instillations for bladder recurrence prevention after radical nephroureterectomy [12].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that a lower Ki-67 LI in ductal hyperplasia under metformin in women with abdominal obesity, the hallmark of insulin resistance, in line with cancer tissue. Thus, metformin selectively decreased Ki-67 in Human Epidermal Growth factor Receptor 2 (HER2)-positive cancers and in women with extra markers of insulin resistance [11]. Interestingly, recent study confirmed that patients with low Ki-67 expressions, negative epidermal growth factor receptor staining and preoperative positive urine cytology appear to be more sensitive to intravesical instillations for bladder recurrence prevention after radical nephroureterectomy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it is important to know whether mTOR activation is related to the recurrence of these tumors in obese individuals and whether mTOR inhibition is helpful to prevent recurrence. mTOR inhibition can be achieved with mTOR inhibitors or metformin, an insulin sensitizer that is widely used in the treatment of type II diabetes 42,43 . Metformin reduces breast tumor growth in diet-induced obese mice 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, all-cause mortality includes deaths from cancer as well. Several studies have shown a significant risk reduction in cancer incidence and mortality among diabetic patients on metformin use relative to other antidiabetic drugs use[ 33 ]. Furthermore, in considering that biguanides demonstrate a better safety profile than most oncology drugs in current anticancer drug use, nonconventional routes for administering diabetobiguanides for cancer treatment has been suggested[ 34 ].…”
Section: Discussionmentioning
confidence: 99%